How to use Alternative and Natural Medicine in the 21st Century Part VII (London Journal of Medical and Health Research, 2025)
For community engagement participants in activities or social support groups can create a sense of belonging and shared understanding. The Integrative and Alternative Therapies are as follows: Acupuncture: A traditional Chinese medicine practice that involves inserting fine needles into specific points on the body. It can be beneficial for pain relief, stress reduction, and improving energy flow. Chiropractic Care: This can help with spinal alignment, which, in turn, supports nerve health and overall physical well-being.Herbal and Natural Remedies: While not a substitute for medical treatment, certain herbs and supplements can support the bodys healing process (e.g., turmeric, ginger, CBD). Body-Mind Connection: Somatic Therapy: This involves the exploration of physical sensations to address stored trauma or emotional blocks within the body. It can include practices like yoga, bodywork, or somatic experiences.Breathwork: Conscious breathing can help activate the parasympathetic nervous system, promoting relaxation and aiding in emotional release. Medical Interventions: While non-traditional therapies are often highly beneficial, there are times when medical interventions such as medications, surgery, or physical therapy are necessary. It is important to collaborate with medical professionals to ensure the best course of action to be taken. Self-Awareness and Self-Care:Listening to the Body: Healing often involves tuning in to your own bodys needs. Setting Boundaries: Protecting your energy and setting boundaries, whether physical or emotional, is key to long-term healing. Everyones healing process is unique, and what works for one person may not work for another. Integrating a combination of these considerations can create a comprehensive approach that nurtures every aspect of ones being.
Keywords: urogenital abnormality; anorectal malformation